Enhanced mobility in PbS quantum dot films via PbSe quantum dot mixing for optoelectronic applications. Issue 15 (26th March 2019) - Hu, Long; Huang, Shujuan; Patterson, Robert; Halpert, Jonathan E.
Abstract : PbSe quantum dots are mixed into PbS quantum dots to form mixed quantum dots for enhancing device performance in optoelectronic applications due to improved charge mobility in solid films. Abstract : PbS quantum dots (QDs) have been used extensively in optoelectronic devices such as solar cells, photodetectors and phototransistors. However, the mobility of charges in PbS QD solid films still limits their performance in many optoelectronic applications. To improve the PbS QD optoelectronic device performance, a small amount of PbSe QDs was mixed into PbS QDs to form a mixed quantum dot solution for fabrication of solar cells and photodetectors. Improvement in charge mobility arises from the higher mobility in PbSe QDs than in PbS, due to their larger exciton radius. The power conversion efficiency of the mixed QD solar cells (mixed PbS and PbSe) improved to 9.4%, compared to 8.8% for a pure PbS QD solar cell and 7.8% for a pure PbSe QD solar cell. Photodetectors were used to investigate the responsivity of pure PbS and the mixed QD photodetector, showing that the responsivity of the mixed QD photodetector was improved to 1.50 from 1.20 μA W −1 . Finally, field effect transistors were used to determine the carrier mobility of PbS, PbSe and their mixtures, demonstrating that the PbSe carrier mobility, at 0.03 cm 2 V −1 s −1, was 8-fold higher than that of pure PbS, at 0.004 cm 2 V −1 s −1 . The mixed film mobility at 0.006 cm 2 V −1 s −1 for 5% PbSe:PbS devices was also higher than that of pure PbS by ∼50%. Overall, the improved device performance is attributed to the improved mobility of mixed QD films due to the presence of PbSe. This leads to the formation of a larger electronic coupling between neighbouring nanocrystals, facilitating charge transport.